2011
DOI: 10.1103/physreva.84.053637
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium and local detection of the normal fraction of a trapped two-dimensional Bose gas

Abstract: We propose a method to measure the normal fraction of a two-dimensional Bose gas, a quantity that generally differs from the non-condensed fraction. The idea is based on applying a spatially oscillating artificial gauge field to the atoms. The response of the atoms to the gauge field can be read out either mechanically from the deposited energy into the cloud, or optically from the macroscopic optical properties of the atomic gas. The local nature of the proposed scheme allows one to reconstruct the spatial pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 80 publications
(130 reference statements)
0
13
0
Order By: Relevance
“…In fact, a quantitative measurement of the superfluid density is more generally an open question in the field of ultracold atomic gases. This is an active area of current research, 54,55 and one big hope is that in the near feature it will be possible to perform both types of measurements on identically prepared atomic samples, thus providing a direct experimental comparison of di↵erent theoretical definitions of superfluidity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a quantitative measurement of the superfluid density is more generally an open question in the field of ultracold atomic gases. This is an active area of current research, 54,55 and one big hope is that in the near feature it will be possible to perform both types of measurements on identically prepared atomic samples, thus providing a direct experimental comparison of di↵erent theoretical definitions of superfluidity.…”
Section: Discussionmentioning
confidence: 99%
“…Ho and Zhou [22] showed that the superfluid density can be extracted from images of rotating clouds. John, Hadzibabic and Cooper [23] identified a global spectroscopic measure of superfluidity, while Carusotto and Castin [24] investigated a local probe.…”
Section: Experimental Probes Of ρSmentioning
confidence: 99%
“…Moreover, exploiting the polarization degree of freedom of polaritons, formation of spin domains [23] and half soliton trains [37][38][39] have been predicted. Finally, from a more general perspective, as the response of a quantum fluid to a phase perturbation is quantitatively related to its superfluid fraction [20,40,41], our experiment opens the way to the experimental measurement of this quantity, crucial in the theory of driven dissipative quantum fluids [42].…”
mentioning
confidence: 99%